Training of Karamunting Fruit Processing as Natural Dyes in the PKK Group in Tarakan City - Jumiati, Elly; Mardhiana, Mardhiana (Universitas Muhammadiyah Palembang, 2021)
The agricultural sector is a source of income for residents in Tarakan City, especially SMEs that process agricultural products into various food products. These products are processed with synthetic dyes, which pose a health risk if consumed in excess overtime. Natural dyes from plants can be used to produce safe food products, one of which is Karamunting fruit. This training aims to provide knowledge as well as the practice of processing Karamunting fruit into natural food and beverage coloring. This training is aimed at partner institutions, namely the PKK group from RT 9 and RT 11 Pamusian Village, Central Tarakan District, Tarakan City. This activity is carried out using training and mentoring methods. The method used is the lecture method, with the practice being evaluated with a questionnaire to measure the effectiveness of the activities to increase the knowledge and skills of participants. The results of this activity are that 1) participants have a positive perception of the training provided; 2) participants gain new insights and knowledge about the benefits and efficacy of Karamunting fruit. 3) Participants gain new skills and experience; 4) Participants interested in expanding business opportunities for Karamunting fruit processing.